Seawater carbonate chemistry during POLARSTERN Cruise PS111 (ANT-XXXIII/2) - Silke Lischka; Jan Michels; Lennart Thomas Bach; Katharina Csenteri; Sonja Konschak; Stanislav N Gorb (PANGAEA, 2025)
The present dataset provides depth profiles of the carbonate system parameters determined on water bottle samples collected alongside the CTD casts during PS111 covering pteropod collection depth and beyond. The carbonate system was calculated with the R package extquotesingleseacarb extquotesingle from measured TA/DIC and TA/pH pairs, respectively. Included in this dataset are also concentrations of silicate, phosphate and chlorophyll a. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were downloaded from the PANGAEA dataset (see Source). In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-05-23.